ORGANIZATIONAL ACTIVITIES TO STIMULATE THE ENTREPRENEURIAL ACTIVITY IN TOURISM - Tleuberdinova А. Т.; Shayekina Zh. M.; Salauatova D. M.; Pratt S. (Scientific Journal of Pedagogy and Economics, 2019)
The purpose of the work is to form an organizational mechanism to stimulate entrepreneurial activity in the tourism sector. For this was determined the role of each subject of the mechanism, in particular, the state and the private sector. The article analyzes the current legislation in the field of tourism and other measures to stimulate tourism entrepreneurship in Kazakhstan and countries with high tourist flow. Moreover, the experience that can be applied in the conditions of development of tourism in Kazakhstan. The result of the work was the formation of the organizational elements of a mechanism to stimulate entrepreneurship in tourism based on the experience of countries with highly developed tourism. Within the framework of individual organizational elements are determined specific actions (measures) and the final result of their implementation. The field of application of the research results is the activity of subjects of the tourist industry at all levels: the state, private business, industry organizations, infrastructure support. The research results will help to use the huge tourist and recreational potential of Kazakhstan, by increasing the activity of entrepreneurs in tourism.